Моніторинг рівня комплаєнс-безпеки промислового підприємства - Кобєлєва, Тетяна Олександрівна (My University, 2019)
У статті розглянуто питання забезпечення економічної безпеки промислового підприємства. Розглянуто фактори, які в найбільшій мірі впливають на стан економічної безпеки. Обґрунтовано важливість та необхідність забезпечення комплаєнс-безпеки промислового підприємства. Обґрунтовано теоретико-методичні положення моніторингу основних показників комплаєнс-безпеки промислового підприємства з використанням арктангенціальної функції. В основу моніторингової функції покладено показники волатильності економічної та комплаєнс-безпеки як безпосередньо даного промислового підприємства та його найближчого бізнес-оточення, так і всієї країни в цілому. Проведено дослідження та аналіз інтервалу значень моніторингової модель-функції та визначено найбільш характерні (реперні) ситуації при дослідженні комплаєнс-безпеки промислового підприємства.

The article deals with the issue of ensuring the economic security of an industrial enterprise. The factors that most influence the state of economic security are considered. The importance and necessity of ensuring the compliance safety of the industrial enterprise is substantiated. The theoretical and methodological provisions of monitoring the main indicators of the compliance of the safety of an industrial enterprise with the use of the arctangential function are substantiated. The monitoring function is based on the volatility indicators of economic and compliance security of both the industrial enterprise and its immediate business environment, as well as the whole country as a whole. Research and analysis of the interval of values of the monitoring model-function is carried out and the most characteristic (benchmark) situations are determined in the study of the compliance safety of an industrial enterprise.
Monitoring the level of compliance of the industrial enterprise
Keywords: економічна діяльність; аркетангенціальна функція; управління; фінанси; compliance; economic security; monitoring; function; industrial enterprises